Studies on Amines of Hurulla (Amblygaster sirm) Do They Cause Allergic Reactions of Hurulla? - Perera, P. Shiromi; Jansz, E.R.; Peiris, H. (My University, 2002)
Past studies stated that consumption ofhurulla (Amblygaster sirm) gave an adverse reaction to tuberculosis patients treated with isoniazid drugs and that the cause may be tyramine. In order to test this hypothesis fresh hurulla samples were tested for histamine and tyramine with and without storage at room temperature using TLC and enzymatic methods. Only traces of tyramine (RfO.88) were found in only 5% of the samples ofhurulla even in the presence of exogenous tyrosine. However, histamine (Rf 0.63) was detected and it was low, 0.34 mg/g of fish. Many other free amino acids were detected on keeping the fish at room temperature. The bacteria producing these amines were isolated from the fish and cultured in a liquid medium. TLC was carried out from these bacterial supernatants to detect histamine. Histamine spots were then quantified by (I) ninhydrin reaction using a spectrophotometer at 570nm or densitometer. (II) Using an ELISA technique. (III) Histaminase assay. All forty-four bacterial colonies isolated were tested for histamine production from histidine. Eleven colonies showed> 0.8mg/m!. However studies with this culture in the log phase of the growth showed that the bacteria produced maximum histamine at 24 hours. However histamine content declined thereafter and was not detected in a 48 h culture. Adjusting pH to 1to solubilize histamine complex increased histamine levels. Addition of EDTA (0.005mg.ml-') increased histamine content with the age of supernatant indicating that chelation could prevent the breakdown of histamine decarboxylase. There was no evidence of breakdown of histamine or tyramine. Studies show that tyramine is not the cause for adverse reactions with isoniazid drugs. Although the histamine content is low, it may contribute to allergic reactions.
Keywords: Amblygaster sirm; Allergenicity; Tyramine; Histamine